Effective strategies for increasing citation frequency - Ale Ebrahim, N.; Salehi, H.; Embi, M.A.; Habibi Tanha, F.; Gholizadeh, H.; Motahar, S.M.; Ordi, A. (Canadian Center of Science and Education, 2013)
Due to the effect of citation impact on The Higher Education (THE) world university ranking system, most of the researchers are looking for some helpful techniques to increase their citation record. This paper by reviewing the relevant articles extracts 33 different ways for increasing the citations possibilities. The results show that the article visibility has tended to receive more download and citations. This is probably the first study to collect over 30 different ways to improve the citation record. Further study is needed to explore and expand these techniques in specific fields of study in order to make the results more precisely.